Counting growth factors in single cells with infrared quantum dots to measure discrete stimulation distributions - Phuong Le (Nature Portfolio, 2019)
Measuring growth factors in single cells at physiologically relevant stimulation doses is challenging. Here the authors use fluorescent quantum dots and calibrated three-dimensional deconvolution microscopy to digitally count growth factors in single cells and reveal stimulation distributions in cancer cells.